Effects of music intervention combined with progressive muscle relaxation on anxiety, depression, stress and quality of life among women with cancer receiving chemotherapy: A pilot randomized controlled trial. - Khanh Thi Nguyen; Huong T X Hoang; Quang V Bui; Dorothy N S Chan; Kai C Choi; Carmen W H Chan (PLoS ONE, 2023)
Beneficial effects of music intervention and progressive muscle relaxation alone on psychological issues were reported, however, studies evaluating their combined effects are limited. This study aimed to investigate the feasibility, acceptability and preliminary effects of music intervention combined with progressive muscle relaxation on anxiety, depression, stress, and quality of life among breast and gynaecological cancer patients receiving chemotherapy. Methods The study was carried out from March to May 2022 in an oncology hospital in Vietnam. A single-blinded randomized controlled trial was conducted among 24 women with breast and gynaecological cancer undergoing chemotherapy. The intervention group (n = 12) received a face-to-face training program about music listening and progressive muscle relaxation skills. They then performed the self-practice daily at home for three weeks. The control group (n = 12) received standard care, including health assessment, regular health advice and nutrition consultation. Ten participants in the intervention group were interviewed with open-ended questions to explore the acceptability of the intervention. Anxiety, depression and stress were measured using the Depression Anxiety Stress Scale, while The Functional Assessment of Cancer Therapy-General was used to evaluate the quality of life. The outcome measurements were collected at baseline (T0), post-intervention (3rd week, T1) and follow-up (6th week, T2). Appropriate descriptive statistics were used to depict the outcome measures across study time points. Results A total of 24 patients were eligible to join, and 20 of them completed the study. Greater reductions in anxiety, depression and stress were observed in the intervention group than in the control group at T1 and T2. Greater improvements on quality of life were found in the intervention group than control group at T1 and T2 with respect to T0. The content analysis supported the acceptable intervention of participants through two themes, perceived beneficial effects on psychological and physical health and willingness to keep practising in the future. Conclusions Implementing music intervention combined with progressive muscle relaxation is feasible and had a trend in reducing anxiety, depression and stress levels. A larger scale randomized controlled trial is needed to confirm the effect of the intervention on outcomes. Trial registration This trial was registered on ClinicalTrials.gov with ID: NCT05262621.